Recycling of Cooking Oil Waste into Reactive Polyurethane for Blending with Thermoplastic Polyethylene - Anika Zafiah M. Rus; N. Syamimi M. Salim; N. Haiza Sapiee (International Journal of Polymer Science)
Driven by the need of growing to a more sustainable and environmentally friendly future, this research is started by mixing in-house produced biorenewable polymers (BP) from waste cooking oil with the standard low density polyethylene (LDPE) and high density polyethylene (HDPE) via melt-mixing at low ratios. These mixtures are then compounded via injection molding to produce tensile samples. By using the quality of individual compounds injected, the parameters obtained for all ratios of LDPE/BP were the same with neat LDPE whereas some adjustments were required for the HDPE/BP compounds. The corresponding mechanical behaviors of each ratio were also examined and the results showed that both tensile strength and strain of the LDPE/BP were better than neat LDPE. On the other hand, increasing the BP content in HDPE/BP will increase the toughness of the compound if compared to neat HDPE. Therefore, not only does the presence of BP provide renewable properties, but it also improves the mechanical properties. Moreover, the processing temperature and composition of BP will both influence the quality and mechanical behavior of the product made. Thus, this study may aid any intention on processing these in-house produced polymers by injection molding.